2014
DOI: 10.1136/bcr-2014-203594
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acidosis in diabetic ketoacidosis

Abstract: We describe the case of a 22-year-old man with insulin-dependent diabetes, who was admitted to the emergency department with hypotension, unconsciousness and a severe combined diabetic ketoacidosis (DKA) and lactic acid acidosis. In the discussion, we focus on the pathophysiological mechanisms underlying lactic acidosis in DKA, and we elaborate on the prognostic value of hyperlactataemia on such occasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…The positive correlation of IPG with lactate as seen in our patients support the possible role of hyperglycemia, in causing lactate elevation, possibly via glyoxalase pathway involving intermediate metabolite methylglyoxal formation and its subsequent conversion into lactate. [ 7 ] This relationship of IPG with lactate demonstrated in our study is in agreement with the findings reported in literature by other investigators.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The positive correlation of IPG with lactate as seen in our patients support the possible role of hyperglycemia, in causing lactate elevation, possibly via glyoxalase pathway involving intermediate metabolite methylglyoxal formation and its subsequent conversion into lactate. [ 7 ] This relationship of IPG with lactate demonstrated in our study is in agreement with the findings reported in literature by other investigators.…”
Section: Discussionsupporting
confidence: 94%
“…Elevated lactate is a common finding in DKA[ 5 6 ] and is generally thought to result from anaerobic glycolysis due to relative tissue hypo-perfusion and hypoxemia; however, other pathophysiological mechanisms are also thought to be responsible. [ 5 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acidosis is a common finding in diabetic ketoacidosis (DKA) and may be multi-factorial in origin, due to metformin use, D-lactate production in erythrocytes (discussed later) and L-lactate production due to increased anaerobic glycolysis [43]. Lactic acidosis has been described in association with hematological malignancies and solid tumors; proposed mechanisms include increased glycolytic activity of the tumor cells (Warburg effect), tumor tissue hypoxia and decreased clearance of lactate due to liver metastases [40,[44][45][46].…”
Section: Causes and Classification Of Lactic Acidosismentioning
confidence: 99%
“…Insulin normally inhibits ketogenesis, hence in lack of insulin ketone products are created which can lead to metabolic acidosis. 18 Elevated lactate levels are often seen in diabetic ketoacidosis, and those are consequence of inadequate tissue perfusion (due to decrease in intravascular volume, presence of micro- and macroangiopathy, increase in glycolyzed hemoglobin, and abnormal platelet function). Further, hypoxemia stimulates process of anaerobic glycolysis where pyruvate is metabolized to lactate along with 2 molecules of adenosine triphosphate (ATP).…”
Section: Discussionmentioning
confidence: 99%